Challenging cavalier perspective: an iconological study of visual perception of depth in Chinese representational space - Xiao, Jing (2013)
Cavalier Perspective has previously been described as merely a pictorial technique of spatial representation within the history of Chinese painting. It is a common belief that this unique visual system is capable of providing an experience of three-dimensional spatial perception in both representational art and actual space, in a manner similar to technique of foreshortening and perspective in post-renaissance western art. However, as Chinese ancient artists have a different understanding of geometry and philosophy, it is difficult to either define the origin and nature of the technique itself or to identify which particular visual phenomena it is intended to communicate, when artists transform three-dimensional space into two-dimensional surface information. The thesis begins by presenting an iconological analysis of the Chinese visual representation of space, in order to develop this visual study into a psychological analysis of the perception of three-dimensional form. To redefine Cavalier Perspective, it is necessary to firstly conduct a historical survey based on available visual evidence of both architecture and landscape representation. In both cases, the represented objects are transformed into flattened forms; and a psychological consequence thus appears involving the loss of a sense of depth in vision, which consequently contributes to the psychology of visual perception. To reassemble, and thus reactivate a similar perception in the representation of space, Chinese ancient artists are also believed to have created specific visual schemes to help reconstitute the perception of depth; thus rendering pictorial space perceptible. Cavalier Perspective is seen as just such a perceptual system. Consequently, the theoretical part of the thesis conducts an iconological study by elaborating a hierarchy of form, technique, and scheme in the history of Chinese spatial representation. After that, a theoretical association is formulated between iconology and visual perception, in which visual techniques are identified as potential cues to indicate depth. The translation between visual technique and depth cue appears so compulsive for both modem scholars and ancient artists that, to a certain extent, the progress of the visual arts could be described as the discovery of techniques for presenting depth through purposive patterns of form. Symbolic images are therefore seen to have their concrete formal basis established upon both pictorial idea and, more importantly, the psychology of visual perception. The thesis aspires to challenge CP by means of this formal analysis. Whether it belongs to a simple technique or a sophisticated visual scheme of ancient Chinese artists; the representational space of geometry; the making of visual perception by means of technical implements; and the bodily experience in actual space, are all shown to be indispensible parts of the present research. A concluding case study of the Chinese landscape garden gives a further demonstration that the pictorial ideas and visual techniques that once contributed to the iconological and psychological understanding of Chinese painting have also delivered an idealised form of spatial perception within the garden - where the sense of depth is firstly eliminated, and then artistically reconstituted. In this way, the nature of cavalier perspective will therefore have been explored on two levels - in the form of both spatial representation and bodily perception in actual space.